Identifikasi Komponen Antibakteri Pada Ekstrak Buah Takokak Menggunakan Kromatografi Lapis Tipis - Hilda Utami Anwar; Nuri Andarwulan; Nancy Dewi Yuliana (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2017)
. Turkey berry (Solanum torvum Swartz) is one of medicinal plants and indigenous vegetables which grows abundantly in Indonesia. It has been known to have antibacterial activity against some pathogen bacteria, including Bacillus cereus. The aim of this study was to determine turkey berry’s metabolites that have antibacterial activity by TLC method. The dried turkey berry was extracted by eight different combinations of methanol and water. These extracts were then divided into two parts: for antibacterial activity analysis and for TLC analysis. Extract with good antibacterial activity and showed more spots in TLC was further identified by two-dimentional TLC. The Rf score of this extract was also compared with reference compounds. F1 extract which was extracted by methanol:water (1:0) showed the highest diameter of inhibition. It also had more TLC spots than other extracts. F1 extract was then chosen to be identified by two dimentional TLC. It showed 14 sub-spots which have maximum absorption at 200-400 nm. Some sub-spots of F1 extract also showed similar Rf score with reference compounds. Based on its TLC profile, F1 extract contain saponin, gallic acid, quercetin, myricetin, kaempferol, and apigenin. However, since TLC has limited resolution, it is possible that F1 contains other flavonoids and phenolic acids that may also responsible for its antibacterial activity.